Kedudukan Rekomendasi Majelis Disiplin Profesi Sebagai Quasi-Penyelidikan Dalam Penyelesaian Sengketa Medik di Indonesia - Fitira, Annisa; Subekti, Rahayu; Isharyanto, Isharyanto (Jurnal Hukum IUS QUIA IUSTUM, 2025)
This paper examines the legal stance of the Professional Disciplinary Council in the medical dispute resolution system based on Law Number 17 of 2023 on Healthcare and its derivative regulations. This study employs a normative juridical research method with a critical analysis of the provisions of Article 308 paragraphs (5) and (6) of the Healthcare Law, and compares them with the concept of quasi-judicial bodies in the legal literature. The main focus of this study is to understand in depth the role, authority, and legal implications of the existence of the Professional Disciplinary Council as part of the medical dispute resolution mechanism, especially in the context of the relationship between health worker professionalism and the criminal justice system. The results of the study indicate that the Professional Disciplinary Council has an important role as a quasi-investigative institution, namely conducting ethical and professional assessments of alleged disciplinary violations by health workers, and providing recommendations before the criminal investigation process is carried out. However, these recommendations is yet to have any legally binding force, thus creating legal ambiguity and potentially triggering tensions between professional institutions and law enforcement officials. To address these problems, this study offers an ideal model for medical dispute resolution that upholds professional justice and legal justice in a balanced manner. The need for normative recognition of the Council's role in the Bill of Criminal Procedure Code (RUU KUHAP) is emphasised, as well as improvements to the institutional design to ensure clarity in mechanisms, boundaries of authority, and synergy between institutions. This is expected to ensure the resolution of medical disputes is fair and accountable, guarantees the protection of the dignity of healthcare workers, and provides legal certainty for patients.